Olá!
Vejamos:
2x + 3y = 4
-5x - 2y = 1
2x = 4 - 3y
x = [tex]\frac{4-3y}{2}[/tex]
-5x - 2y = 1
-5[tex](\frac{4-3y}{2} )[/tex] - 2y = 1
[tex]\frac{-20+15y}{2}[/tex] - 2y = 1
[tex]\frac{-20}{2}[/tex] + [tex]\frac{15y}{2}[/tex] - 2y = 1
[tex]\frac{-20}{2}[/tex] + [tex]\frac{15y}{2}[/tex] - [tex]\frac{4y}{2}[/tex] = [tex]\frac{2}{2}[/tex]
-20 + 15y - 4y = 2
15y - 4y = 2 + 20
11y = 22
y = 22 ÷ 11
y = 2
2x + 3y = 4
2x + 3 · 2 = 4
2x + 6 = 4
2x = 4 - 6
2x = -2
x = -2 ÷ 2
x = -1
Encontramos o par ordenado (-1, 2) que corresponde ao ponto C no plano cartesiano.
Abraços!